Technique: Imaging Earliest Tooth Development in 3D Using a Silver‐Based Tissue Contrast Agent. Issue 2 (19th December 2013) - Raj, Muhammad T.; Prusinkiewicz, Martin; Cooper, David M.L.; George, Belev; Webb, M. Adam; Boughner, Julia C.
ABSTRACT Looking in microscopic detail at the 3D organization of initiating teeth within the embryonic jaw has long‐proved technologically challenging because of the radio‐translucency of these tiny un‐mineralized oral tissues. Yet 3D image data showing changes in the physical relationships among developing tooth and jaw tissues are vital to understand the coordinated morphogenesis of vertebrate teeth and jaws as an animal grows and as species evolve. Here, we present a new synchrotron‐based scanning solution to image odontogenesis in 3D and in histological detail using a silver‐based contrast agent. We stained fixed, intact wild‐type mice aged embryonic (E) day 10 to birth with 1% Protargol‐S at 37°C for 12–32 hr. Specimens were scanned at 4–10 µm pixel size at 28 keV, just above the silver K‐edge, using micro‐computed tomography (µCT) at the Canadian Light Source synchrotron. Synchrotron µCT scans of silver‐stained embryos showed even the earliest visible stages of tooth initiation, as well as many other tissue types and structures, in histological detail. Silver stain penetration was optimal for imaging structures in intact embryos E15 and younger. This silver stain method offers a powerful yet straightforward approach to visualize at high‐resolution and in 3D the earliest stages of odontogenesis in situ, and demonstrates the important of studying the tooth organ in all three planes of view. Anat Rec, 297:222–233, 2014. © 2013 Wiley Periodicals, Inc.